Assessing the Government's Commitment to Achieving Ecological Justice for Society - Sudiana, Anak Agung KT; Ni Putu Noni Suharyanti; Umirov Fitrat Faxriddinovich (Lembaga Contrarius Indonesia, 2025)
Ecological justice is essential for maintaining environmental sustainability and ensuring fair access to natural resources. However, its implementation is often hindered by economic and political interests, weak institutional capacity, and inadequate legal frameworks. This research evaluates the Indonesian government's commitment to ecological justice by analyzing the effectiveness of its environmental policies. Using a normative legal research method with a conceptual approach, legislative analysis, and comparative study, this study examines Indonesia’s policy framework and governance challenges. The findings show that despite various policy commitments, regulatory weaknesses, insufficient protection of indigenous rights, and limited public participation hinder progress. Indonesia prioritizes economic growth over environmental sustainability, leading to ecological degradation. Industrial dominance, legal loopholes, weak law enforcement, and corruption further exacerbate these issues. Meanwhile, Saudi Arabia has demonstrated a strong commitment through initiatives like the Saudi Green Initiative and major investments in renewable energy. To achieve ecological justice, Indonesia must strengthen environmental policies, improve law enforcement, and enhance cross-sector collaboration. By adopting Saudi Arabia’s targeted strategies, increasing transparency, and integrating green technologies, Indonesia can accelerate its transition toward sustainable and inclusive development.